A Cross-Sectional Survey of Lower Urinary Tract Symptoms and Its Association with Lifestyle and Toiletting Behaviour of Young Female Undergraduates in South-West Nigeria - A., Zaki Desmond; M., Karaga Ali; M., Dan Inu Audu; M., Williams Torojah; Rapheal, Christopher; M., Olugbenga Mary; M., Audu Anthony; A., Owolabi Jeremiah; H., Jeremiah Janet (Darul Yasin Al Sys, 2025)
Introduction: Previous studies have explored Lower Urinary Tract Symptoms (LUTS) among elderly females and the middle aged, yet limited studies have been carried out on the apparently healthy younger female population especially in Nigeria. This study investigated the prevalence of LUTS, and its association with toileting behaviours, and lifestyle of young Nigerian female undergraduates. Methods: This cross-sectional study was conducted among 345 female undergraduates of Bowen University Iwo, Osun State, Nigeria aged 17 to 24 years. All participants completed the International Consultation on Incontinence Modular Questionnaire for Female Lower Urinary Tract Symptoms (ICIQ-FLUTS), socio-demographic form and a toileting behavior data form. Spearman’s correlation test and Chi square were used for inferential statistics at 0.05 level of significance. Results: There was no significant relationship between LUTS and each of caffeine intake, carbonated drink intake and participation in physical activities. However, there was a significant association between sexual activity and filling symptoms (p=0.014), and incontinence symptoms (p=0.020), but no significant association with voiding symptoms (p=0.668). There was also no significant association between LUTS and toileting behaviour of participants. Conclusion: This study found high prevalence of LUTS among young female undergraduates. There was also an association between sexual activity and LUTS among participants. However, intake of caffeine and carbonated drinks, as well as lack of physical activity were found not be associated with LUTS in this population. Similarly, toileting behaviours had no association with LUTS, however, an experimental study design is recommended to further explore this.